Full catastrophe living: how to cope with stress, pain and illness using mindfulness meditation - Kabat-Zinn, Jon (London Piatkus, 2020)
This classic, ground-breaking work which gave rise to a whole new field in medicine and psychology shows you how to use medically proven mind-body approaches derived from meditation and yoga to counteract stress, establish greater balance of body and mind, and stimulate well-being and healing.
Keywords: Psychology; Meditation